Rheological Properties of Lamellae‐Forming Diblock Copolymers. Issue 7 (4th June 2021) - Tomiyoshi, Yoshinori; Kawakatsu, Toshihiro; Aoyagi, Takeshi; Morita, Hiroshi
Abstract: The present study investigates rheological properties of microphase‐separated lamellar structures formed by unentangled and weakly entangled diblock copolymer melts under a finite amplitude oscillatory shear flow and a steady shear flow. To simulate such a system, dissipative particle dynamics (DPD) simulation is employed to reproduce the lamellar structures, where a multi‐chain slip‐spring model is combined with DPD simulation to mimic entanglement effects. By imposing an oscillatory shear flow, this model enables us to measure storage and loss moduli for three different (parallel, perpendicular, and transverse) lamellar orientations with respect to the flow direction. These orientations display distinctive rheological behaviors, and especially the transverse orientation exhibits a peculiar behavior owing to a finite expansion of the lamellar interfaces, which differs from a previous study. In a steady shear flow, steady shear viscosities of parallel and perpendicular orientations are evaluated. In this case, the orientations of lamellar domains and the local orientation and stretching of bonds near the lamellar interfaces affect the steady shear viscosities. A spatial distribution of entanglements also affects the steady shear viscosities differently from another previous study. Abstract : The rheology of lamellar phase of unentangled and entangled diblock copolymers under a finite amplitude oscillatory shear flow and a steady shear flow is discussed by the dissipative particle dynamics with slip‐springs. The deformations of the lamellar interfaces, the spatial constraints of junction points of diblock copolymers, and the spatial distribution of the entanglements crucially affect their dynamical behaviors.